Strategi Pemasaran Benih Padi pada UD Tani Sejati di Kecamatan Blahbatuh Kabupaten Gianyar - SUGIHARTA, I NYOMAN; DARMAWAN, DWI PUTRA; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.4, Oktober 2016, 2016)
The Marketing Strategy Rice Seed At UD Tani Sejati In The District Blahbatuh Gianyar The agricultural sector is the most important sector in both the long-term economic development as well as for short-term economic recovery. UD Tani Sejati is one of trader that produce rice seeds.  The purpose of this research are identifying the internal factors and eksternal factors; knowing common strategy in improving the marketing of rice seeds; and finding out how an alternative strategy in improving the marketing of rice seeds. Research scope is covering environmental analysis of internal and eksternal that affects marketing at UD Tani Sejati. Identification of UD Tani Sejati internal faktor in the form of strength and weakness, and eksternal factor in the form of opportunities and threat. Common strategy produced by Matriks IFAS-EFAS be on a circle quadrant V it means UD Tani Sejati in a position can develop the strategy of maintaining and maintenance products, develop strategies for market and product development strategy. The result of SWOT matrix obtained alternative strategy, namely : strategy S-O increase the volume of procurement and disbursing; strategy W-O inprove education human recources; strategy S-T make coordination with production factor providers and raw materials; strategy W-T optimize the promotion. Need to safety advanced research on the marketing strategy and increase production strategies to be able to do market penetration and raise production capacity.
Keywords: marketing; strategy; rice seed